1972
DOI: 10.1021/jo00970a009
|View full text |Cite
|
Sign up to set email alerts
|

Strained heterocyclic systems. VI. Basicities of some quinoxalines

Abstract: The basicities of a series of 2,3-disubstituted quinoxalines were determined by potentiometric titration in acetic anhydride. A decrease in basicity was observed for those compounds containing a fused, strained ring adjacent to the heteroatoms. Such an effect was consistent with previous interpretations based on orbital rehybridization. In conjunction with the present study, J (13C-H) values were determined for the benzylic protons of acenaphthene and pyracene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…5 The argument is based on the Drude-Nernst equation, These results are in agreement with the concept of cr participation, and we interpreted them in terms of the controversial4 nonclassical ions, in which the positive charge is equally divided between two or more carbon atoms because of symmetry.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…5 The argument is based on the Drude-Nernst equation, These results are in agreement with the concept of cr participation, and we interpreted them in terms of the controversial4 nonclassical ions, in which the positive charge is equally divided between two or more carbon atoms because of symmetry.…”
Section: Methodssupporting
confidence: 79%
“…Catalytic hydrogenation of 4-nitrobenzocyclobutene in absolute EtOH over platinum oxide catalyst afforded 5 in quantitative yield as an orange oil, which was used without further purification:3o GLC (215 OC, 30 mL/min) 7 3.3 (trace), 5 Compound 1 has not previously been reported. Commercially available samples of quinoline, isoquinoline, 2-methylquinoline, 4-methylquinoline, and 6-methylquinoline were vacuum distilled immediately prior to basicity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the reductions of complexes 1, 2 and 3 are thermodynamically more facile than that of complex F (Scheme 1) by 190, 50 and 130 mV, respectively (Table 5). When we compare the acidic property among heterocyclic dithiolene ligands H 2 pydt, H 2 qdt and H 2 ppdt (Scheme 2), we found that the pK a value of pyrazine (H 2 pydt) (0.67) [61] is less than that of quinoxaline (H 2 qdt) (1.03) [62]. Therefore, pyrazine has more electron-withdrawing character than quinoxaline.…”
Section: Electrochemistry Of Model Complexes 1e6mentioning
confidence: 99%
“…Acetyl Received January 7, 1991 The influence of ring strain effects on the basicity of quinolines was fllSt reported in 1967. 3 The initial studies were extended to quinoxalines 4 and, more recently, to 1-azatriptycene. 5 In this report a similar correlation is applied to a series of bicyclic quinoxalines.…”
mentioning
confidence: 99%
“…Strain effects in bicyclic alkanes are weil known 8 (4). Compounds 1-3 were prepared by Iiterature methods; a preliminary acoount of 4 has been reported.…”
mentioning
confidence: 99%